2019
DOI: 10.1016/j.apergo.2018.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Engineering movement into automotive seating: Does the driver feel more comfortable and refreshed?

Abstract: The concept of introducing movement in automotive seating was investigated. Three seat conditions, a control (no movement) and two movement conditions (fore-aft and cushionbackrest) were compared. Movement was introduced at a fixed speed, slow, smooth and within a small range. Ten participants took part in a 60 minute simulated drive for each condition-single blind, repeated measures, and balanced order. Discomfort ratings were collected for six body areas and overall discomfort, together with a wellbeing ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 30 publications
(38 reference statements)
1
8
0
3
Order By: Relevance
“…e importance of anthropometric measurements is highlighted by the fact that driving for extended periods of time inevitably leads to musculoskeletal symptoms and is associated with disorders of the spine, deep vein thrombosis, and similar problems [38][39][40]. Restricted postures, repetitive movements, vibration, continuous attention to the road, and stress are the suspected risk factors for various disorders in drivers [39].…”
Section: Previous Researchmentioning
confidence: 99%
“…e importance of anthropometric measurements is highlighted by the fact that driving for extended periods of time inevitably leads to musculoskeletal symptoms and is associated with disorders of the spine, deep vein thrombosis, and similar problems [38][39][40]. Restricted postures, repetitive movements, vibration, continuous attention to the road, and stress are the suspected risk factors for various disorders in drivers [39].…”
Section: Previous Researchmentioning
confidence: 99%
“…Давление воздуха в шинах коммунальной машины на базе МТЗ-80, рекомендуемое производителем, установленное ГОСТ 7463-2003, а также указанное в руководстве по эксплуатации, корректно варьировать в пределах: для задних колес 0,1-0,18 МПа, для передних колес 0,12-0,26 МПа [4,17,18]. Такие значения давления соответствуют C i заднего колеса 2,7•10 5 … 3,6•10 5 Н/м, переднего колеса 29•10 5 …4,6•10 5 Н/м [18,19].…”
Section: результаты исследованияunclassified
“…4) и в шинах колес заднего моста (рис. 5) в пределах, в которых может сохраняться продолжительность срока службы шин, позволяет снизить величину динамических воздействий на полу кабины и раме машины [19,20]. Изменение величины динамических воздействий на кресле оператора при этом несущественно.…”
Section: результаты исследованияunclassified
“…As an example, Veen et al [6] investigated a seat movement system in which the backrest moved 1.5° backwards and the seat cushion 1° up and down (and back to the starting position) and concluded it had a beneficial effect on the wellbeing of the drivers. An experimental study by the author has shown that there was less reported discomfort with seat movement while driving compared to no seat movement [7]. Using the methods, driving rig and movement conditions standardized from previous studies [7,8], this paper reports on research conducted to understand in more detail the drivers' experience of the seat movement concept.…”
Section: Introductionmentioning
confidence: 99%
“…An experimental study by the author has shown that there was less reported discomfort with seat movement while driving compared to no seat movement [7]. Using the methods, driving rig and movement conditions standardized from previous studies [7,8], this paper reports on research conducted to understand in more detail the drivers' experience of the seat movement concept.…”
Section: Introductionmentioning
confidence: 99%